Barriers and Facilitators of Deprescribing in Indian Geriatric Patients: A Clinical Pharmacist Perspective - N, Nagadeepthi (Indian Journal of Pharmacy Practice, 2026)
The elderly population in India is growing rapidly and is projected to exceed 340 million by 2050. Polypharmacy, defined as the concurrent use of five or more medications, affects 50-79% of Indian geriatric patients and is associated with Adverse Drug Reactions (ADRs), falls, and preventable hospitalisations. Deprescribing, the supervised reduction or discontinuation of medications whose harms outweigh their benefits in the context of an individual patient's goals of care, represents a rational strategy to optimise geriatric pharmacotherapy. Clinical pharmacists, through their training in pharmacotherapy and patient counselling, are well positioned to support these initiatives. This review aimed to identify, categorise, and analyse the barriers and facilitators of deprescribing in Indian geriatric patients from a clinical pharmacist's perspective, and to propose evidence-based recommendations for its advancement. A narrative review was conducted using PubMed, Scopus, Google Scholar, and the Cochrane Library, with studies and guidelines published between 2005 and 2024 included. Barriers were identified at patient, prescriber, and system levels, encompassing fear of disease relapse, low health literacy, therapeutic inertia, fragmented prescribing care, and the absence of India-specific deprescribing guidelines. Facilitators included patient willingness to reduce medications, validated clinical tools, pharmacist-led medication review, shared decision-making, and digital health integration. Deprescribing is feasible in the Indian geriatric context but demands a coordinated, multidisciplinary approach. Clinical pharmacists-particularly Pharm D practitioners-can lead medication review, patient counselling, and interprofessional collaboration. Development of India-specific guidelines and stronger integration of pharmacy services into geriatric care teams are urgently needed.
Keywords: Barriers; Clinical Pharmacist; Deprescribing; Facilitators; Geriatric; India; Medication; Review; Polypharmacy